Demons on the Couch: Spirit Possession, Exorcisms and the DSM-5 by Michael Sersch - Hayen, Todd (Journal of Scientific Exploration, 2020)
Michael J. Sersch’s (2019) Demons on the Couch: Spirit Possession, Exorcisms and the DSM-5 is an immaculately researched and referenced treatise on possession and exorcism presented through the lens of modern psychotherapy and the DSM-5 (the diagnostic bible of the mental health field.) Sersch states in his introduction: In writing this book, I hope to answer why demonic possession has held a cultural fascination for over two millennia as well as how clinicians can successfully and ethically deal with patients who legitimately believe they are possessed by a spiritual force. There is also mounting evidence that integrating a patient/client’s worldview into clinical practice, including their spirituality and faith practices, increases their likelihood of getting better (Lund, 2014) which is a position I am overtly advocating. (p. 5) He also claims that he has no desire to attempt to prove or disprove spirit or demonic possession (p. 5). His approach is largely clinical and pedagogical: what does a clinician do with a patient who claims they are possessed? Sersch divides his thesis into three sections, each section dealing with a different aspect of possession and exorcism. The first section, appropriately enough, deals with the history of spirit possession, demon possession, and different forms of exorcism. The second section is more clinical in its approach going into detail on such topics as the different designations for diagnoses found in the various editions of the Diagnostic Statistical Manual (DSM) such as Multiple Personality Disorder (an older label having been replaced with Dissociate Identity Disorder in the fourth edition of the DSM (APA, 1994)). The third section focuses on suggestions for the clinician, again: how does the clinician handle patients claiming to be possessed?